Glass Ionomer Cements for the Restoration of Non-Carious Cervical Lesions in the Geriatric Patient - Kampanas, Nikolaos-Stefanos (J Funct Biomater, 2018)
Background: The restoration of non-carious cervical lesions in geriatric patients is a demanding process. Glass ionomer cements can be promising materials for the management of these lesions in older adults. The aim of this literature review is to present the benefits of glass ionomers and how they can be used for the restoration of non-carious cervical lesions of older adults depending on the geriatric patient’s profile. Data sources: All available in vitro and in vivo studies from Google Scholar, PubMed and Scopus search engines corresponding to glass ionomer cements, geriatric dentistry, elderly patients, and non-carious lesions as key words were reviewed. Data synthesis: The advantages of glass ionomer cements, such as good retention and fluoride release, make them suitable for the restoration of non-carious cervical lesions. However, several factors related to the geriatric patient’s profile determine the most suitable material type. Conclusion: In general, the resin modified glass ionomer cements (RMGICs) appear to be preferred, but under certain circumstances the use of the conventional product is more appropriate, despite its poorer mechanical features. Further studies are required for more reliable data analysis and clinical interpretation of the relevant results.